Lactobacillus acidophilus inhibits the TNF-α-induced increase in intestinal epithelial tight junction permeability via a TLR-2 and PI3K-dependent inhibition of NF-κB activation - Haque, Mohammad; Kaminsky, Lauren; Abdulqadir, Raz; Engers, Jessica; Kovtunov, Evgeny; Rawat, Manmeet; Al-Sadi, Rana; Ma, Thomas Y. (Frontiers in Immunology, 2024)
Defective intestinal epithelial tight junction (TJ), characterized by an increase in intestinal TJ permeability, has been shown to play a critical role in the pathogenesis of inflammatory bowel disease (IBD). Tumor necrosis factor-α (TNF-α) is a key pro-inflammatory cytokine involved in the immunopathology of IBD and has been shown to cause an increase in intestinal epithelial TJ permeability. Although TNF-α antibodies and other biologics have been advanced for use in IBD treatment, these therapies are associated with severe side effects and have limited efficacy, and there is an urgent need for therapies with benign profiles and high therapeutic efficacy. Probiotic bacteria have beneficial effects and are generally safe and represent an important class of potential therapeutic agents in IBD. Lactobacillus acidophilus (LA) is one of the most used probiotics for wide-ranging health benefits, including in gastrointestinal, metabolic, and inflammatory disorders. A specific strain of LA, LA1, was recently demonstrated to have protective and therapeutic effects on the intestinal epithelial TJ barrier. However, the mechanisms of actions of LA1 remain largely unknown. The primary aim of this study was to investigate microbial-epithelial interactions and novel signaling pathways that regulate the effect of LA1 on TNF-α-induced increase in intestinal epithelial TJ permeability, using cell culture and animal model systems. Pre-treatment of filter-grown Caco-2 monolayers with LA1 prevented the TNF-α-induced increase in intestinal epithelial TJ permeability by inhibiting TNFα-induced activation of NF-κB p50/p65 and myosin light chain kinase (MLCK) gene and kinase activity in a TLR-2-dependent manner. LA1 produced a TLR-2-and MyD88-dependent activation of NF-κB p50/p65 in immune cells; however, LA1, in intestinal cells, inhibited the NF-κB p50/p65 activation in a TLR-2-dependent but MyD88-independent manner. In addition, LA1 inhibition of NF-κB p50/p65 and MLCK gene was mediated by TLR-2 pathway activation of phosphatidylinositol 3-kinase (PI3K) and IKK-α phosphorylation. Our results demonstrated novel intracellular signaling pathways by which LA1/TLR-2 suppresses the TNF-α pathway activation of NF-κB p50/p65 in intestinal epithelial cells and protects against the TNF-αinduced increase in intestinal epithelial TJ permeability.